Pengaruh Fonologi Pada Kajian Fonetik Dalam Bahasa Indonesia - Ihsan, Raihan Fauzil; Siagian, Irwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The study of the relationship between phonology and phonetics has an important role in understanding sound systems in Indonesian. Phonology studies sound structure and its relation to meaning, while phonetics analyzes sound physically. In the context of the Indonesian language, the influence of phonology on phonetic studies can be seen in the analysis of allophones and sound variations, phonetic changes, language learning, and linguistic research. This study uses a qualitative research method, which means that this research describes qualitatively the sounds that affect other sounds and describes the voices that are affected. Every sound that is influenced by other sounds will be described and whether these sounds are influenced by sounds in Indonesian. Therefore, the combination of phonological and phonetic studies in Indonesian makes a significant contribution to the understanding and research of the phonetic aspects of the language.